The Baroque, the figure of the narrator and composition in The predominance of faith - Escobar Tapia, Héctor Omar (2024)
This article develops a reading from narratology and the formal elements of painting to account for the particularities of the novel The predominance of faith (2020) by the Peruvian narrator Gonzalo Portals Zubiate (Lima, 1961-2023). The work establishes relationships between the paintings of the Baroque artist Michelangelo Merisi da Caravaggio (Milan, 1571) and the narrative elements of the novel. In addition, it is proposed that in the novel there is a cynical narrator who hides information from the reader. In this way, the article affirms that the novel The predominance of faith establishes new levels of interpretation and intertextuality.